China's practice of smart city standardisation and assessment - Dapeng Zhang; Xi Wang; Wenge Rong; Yu Yang (IET Smart Cities, 2021)
Abstract Smart city is one of the current trends of city evolvement. Smart city is a systematic project, which needs a holistic approach. As lots of pilot projects have been undertaken by cities, how to assess the ‘smartness’ of a city is of great importance. This study sums China's smart city standardisation and assessment practice, starting from the national policy evolvement, followed by the standardisation system, assessment and its key procedures and concludes with some possible future works regarding smart city standardisation and assessment.